Практична реалізація міжнародних вимог щодо забезпечення електромагнітної сумісності в нормативних документах України - Жаркін, Андрій Федорович; Палачов, Сергій Олександрович; Шкляр, Тетяна Борисівна (НТУ "ХПІ", 2017)
Проведено огляд основних принципів забезпечення ЕМС в електричних мережах, що базуються на розподілі відповідальності між споживачами і електропостачальною організацією. Розглянуто область застосування гармонізованих стандартів, а також базові положення розробленої МЕК триступеневої системи розрахунку норм емісії завад від апаратури різної потужності. Проведено аналіз рівня відповідності нормативної бази України в галузі енергетики міжнародним вимогам щодо забезпечення ЕМС, розглянуті заходи, що необхідні для підвищення якості напруги електропостачання.

The main principles of achieving EMC in power networks, which are based on the division of responsibility between the consumers and the electricity supplier, are reviewed. The scope of application of harmonized standards is considered, as well as the basic provisions of the three-stage system developed by the IEC for the calculation of disturbances emission limits from equipment of various power. The analysis of compliance of the regulatory documents of Ukraine in the field of energetics with international requirements for ensuring EMC was made. The measures that are necessary to improve the quality of the power supply voltage are considered.
Practical implementation of international requirements for EMC in the regulations of Ukraine
Keywords: розподільна мережа; якість напруги; емісія завад; гармонізовані стандарти; electromagnetic compatibility; distribution network; power quality; emission of disturbances; harmonized standards